2005
DOI: 10.1073/pnas.0408354102
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA from giant extinct lemurs confirms single origin of Malagasy primates

Abstract: The living Malagasy lemurs constitute a spectacular radiation of >50 species that are believed to have evolved from a common ancestor that colonized Madagascar in the early Tertiary period. Yet, at least 15 additional Malagasy primate species, some of which were relative giants, succumbed to extinction within the past 2,000 years. Their existence in Madagascar is recorded predominantly in its Holocene subfossil record. To rigorously test the hypothesis that all endemic Malagasy primates constitute a monophylet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 42 publications
5
75
0
3
Order By: Relevance
“…Because we used fossil-tip dating techniques and not every individual with genetic data had a fully sequenced mitochondrial genome, we constrained the topology to reflect the relationships inferred by Karanth et al (10). To time-calibrate the phylogeny, we used two fossil-based prior age calibrations following the methodology of Kistler et al (11).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we used fossil-tip dating techniques and not every individual with genetic data had a fully sequenced mitochondrial genome, we constrained the topology to reflect the relationships inferred by Karanth et al (10). To time-calibrate the phylogeny, we used two fossil-based prior age calibrations following the methodology of Kistler et al (11).…”
Section: Methodsmentioning
confidence: 99%
“…Folivory was inferred to have evolved independently between one and five times, with phylogenetic analyses of ancient DNA demonstrating that Megaladapis, an extinct folivorous lineage, was not a sister to the strictly folivorous Lepilemur clade. Before molecular phylogenetic analyses, the two lineages were considered to form a monophyletic group on the basis of morphology (10). Thus, whereas folivory was initially assumed to have evolved only once in the putative Lepilemur-Megaladapis clade, ancient DNA analysis has revealed that it must have evolved independently at least twice.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…15 N) 1 from extant and recently extinct sympatric lemur species. Isotopic niches reflect aspects of habitat and diet, but in condensed form (e.g.…”
Section: And Dmentioning
confidence: 99%
“…Lemurs represent a prodigious radiation of primates in Madagascar [1,2]. Yet many are at risk of extinction [2], and at least 17 species have vanished during the past 2000 years [3].…”
Section: Introductionmentioning
confidence: 99%